Quality of Using Google Classroom to Support the Learning Processes in the Automation and Programming Course - Abuzant, Maysa; Ghanem, Monji; Abd-Rabo, Ayshi; Daher, Wajeeh (International journal of emerging technologies in learning, 2021)
Virtual and blended learning are suggested as means to support students’ learning of the subject matter. The present study sought to examine how one educational tool for the classroom; specifically Google Classroom, was used by a teacher of automation and programming course in the secondary school. One secondary school teacher and her two students participated in the re-search. The data collection tools were interviews of two types: asking the participants semi-structured questions, and requesting the teacher to show how she used the Google Classroom options to engage her students in online learning. The transcribed interviews were analyzed using thematic analysis depending on the model of Information Systems Success by DeLone and McLean. The research results indicated that Google Classroom contributed to the quality of the learning of the students, which affected positively the teach-er’s and students’ satisfaction and intention to use this educational tool in the automation and programming class. The participants pointed at the benefits of using Google Classroom, which once again influenced positively the par-ticipants’ satisfaction and intention to use it for teaching and learning. The present study showed how a virtual classroom could be utilized in technolo-gy courses. The described phenomenon could give insights, not only to tech-nology teachers but to the teachers of other disciplines, how to utilize virtual and information systems in their teaching in order to enrich students’ learn-ing.